Quantification of Primary Metabolites of Commiphora wightii (Arnott.) Bhandari: Rare Endangered species - Dhawan, Poonam (International Journal of Pharmaceutical & Biological Archive, 2016)
Commiphora wightii (Arnott.) Bhandari is an important medicinal plant of herbal heritage of India. It belongs to family Burseraceae. The plant is an important medicinal plant and is used in large number of ayurvedic preparations to treat variety of diseases. It is mainly used to treat diseases like atherosclerosis, leprosy, pneumonia, rheumatism etc. The gum resin also has aphrodisiac, diuretic and immunostimulant properties. Primary metabolites viz, protein, lipid, carbohydrates and so forth play a key role in metabolic processes such as photosynthesis, respiration and nutrient assimilation. They are used as raw material and food additives. The present study was conducted to investigate biochemical estimation of primary metabolites viz, totalsoluble sugar, starch, lipids, proteins and phenols etc .in vitro plant parts.